Assessing Community Perspectives on Flood Preparedness and Mitigation Strategies in Nigeria - Utsev, Joseph Terlumun; Onyebuchi, Mogbo; Onuzulike, Collins; Akande, Ebenezer Ogirima; Orseer, Ama Moses; Tiza, Michael Toryila (Journal of Novel Engineering Science and Technology, 2024)
This study aims to assess the perspectives of 200 respondents in Makurdi town, Benue State, Nigeria, on flooding using a Likert scale questionnaire. Flooding is a recurring challenge in the area, impacting lives and properties and necessitating effective flood management and mitigation strategies. The questionnaire covers various aspects of flooding, including frequency, property damage, flood warning systems, government efforts, climate change impact, community preparedness, and community-based initiatives. The findings reveal that flooding frequently occurs in Makurdi, emphasizing the urgency for comprehensive flood management strategies. Respondents acknowledge the personal impact of flooding, highlighting the need for effective mitigation measures. Improvement is needed in flood warning systems and government efforts to prevent flooding. Climate change's role in increasing flooding is recognized, emphasizing the importance of climate-resilient strategies. Community awareness and education are essential for reducing flood impacts, while public-private partnerships offer opportunities for collaborative flood management initiatives. The media's role in disseminating flood-related information is crucial. Stricter enforcement of building codes in flood-prone areas and community-based initiatives can contribute significantly to effective flood management. The implications of this study underscore the importance of community engagement, climate-resilient measures, and improved communication. Policymakers and local authorities can use these findings to develop targeted interventions for building a more flood-resilient Makurdi. By adopting proactive measures and community involvement, the town can enhance preparedness and adaptability to future flood scenarios, fostering a safer and more sustainable environment.